Concurrent enhancement of CO2 fixation and productivities of omega-3 fatty acids and astaxanthin in Haematococcus pluvialis culture via calcium-mediated homeoviscous adaptation and biomineralization. (November 2021) - Yu, Byung Sun; Sung, Young Joon; Choi, Hong Il; Sirohi, Ranjna; Sim, Sang Jun
Graphical abstract: Highlights: ExCA activity and CO2 fixation rate were boosted via Ca 2+ -based biomineralization. The production of ω-3 FA was accelerated via Ca 2+ -induced homeoviscous adaptation. Separated pure H. pluvialis could produce high content of astaxanthin sustainedly. CaCO3 crystal enabled H. pluvialis to cultivate under intensive light conditions. The biomineralization-inspired culture tactic could be well applied to large-scale. Abstract: Haematococcus pluvialis has attracted interest as a bio-platform for producing omega-3 fatty acids (ω-3 FA) and astaxanthin that have a great potential as anti-inflammatory drugs. This study aimed to concurrently enhance the CO2 fixation and the productivities of ω-3 FA and astaxanthin, which have been difficult to achieve because of the dissimilar culture methods for each goal, via calcium-mediated homeoviscous adaptation and biomineralization. As a result of 3 mM of Ca 2+ addition, ω-3 FA content was improved by 31% due to Ca 2+ -induced homeoviscous adaptation. Biomineralization was promoted by the extracellular carbonic anhydrase, which resulted in 46.3% improvement in CO2 fixation. CaCO3 from the biomineralization was beneficially re-used in the H. pluvialis culture and triggered 178- and 522-fold increased biomass productivity and astaxanthin content, respectively, thanks to its anisotropic nature. The Ca 2+ -based productivity enhancement strategy was applied to large-scale culture which resulted improvement in overall bioprocess performance.